The Relationship between Cardiovascular System Health and Dementia Events at Ages 50-60 Years at Teluk Kuantan Regional Hospital - Ichwan Alamsyah Lubis; Zaim Anshari (International Journal of Public Health Excellence (IJPHE), 2023)
Dementia is a syndrome in which there is deterioration in memory, thinking, behavior and the ability to perform daily activities. Several studies have shown an association between the development of cognitive impairment and dementia with educational attainment, and lifestyle-related risk factors, such as physical activity, tobacco use, unhealthy diet and harmful alcohol use. Furthermore, certain medical conditions are associated with an increased risk of developing dementia, including hypertension, diabetes, dyslipidemia, obesity and depression. The ideal cardiovascular health score, also referred to as Life's Simple 7, consists of four behavioral indicators of health, and three biologics. This study aims to determine the relationship between the health of the cardiovascular system and the incidence of dementia at the age of 50-60 years at Teluk Kuantan General Hospital. This research was carried out in an analytical nature using a cross-sectional design, which was conducted at the Teluk Kuantan Regional Hospital, in December 2020 - March 2021 and involved 70 respondents. Data obtained by medical records and interviews. Based on the results of the study, the results of the somer s d correlation test obtained p value = 0.000 (p <0.05) so that there was a significant relationship between cardiovascular system health and the incidence of dementia at the age of 50-60 years. There is a Relationship between the Health of the Cardiovascular System and the Incidence of Dementia at the Age of 50-60 Years.